Effectiveness of Green Mussel (Perna viridis) and PAC in Reducing TSS and Turbidity in River Water - Sabrina, Zakkiyah; Amalia, Aussie; Murti, Restu Hikmah Ayu (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Contamination of river water by suspended particles and organic matter increases total suspended solids (TSS) and turbidity, degrading water quality and posing risks to aquatic ecosystems and public health. This study evaluated the performance of chitosan derived from green mussel shells (Perna viridis) compared to polyaluminium chloride (PAC), a conventional coagulant, in reducing TSS and turbidity. Chitosan was selected due to its cationic polymer properties, which are obtained through the conversion of chitin, enhancing its coagulation–flocculation effectiveness. The experiment employed a jar test with variations in pH (5, 7, and 9), coagulant dosage, and standardized mixing protocols. Results showed that chitosan achieved optimal performance at pH 5 with a 150 mg/L dosage, resulting in 82% TSS removal and 87% turbidity reduction. In contrast, PAC performed best at pH 7 with a 20 mg/L dosage, achieving 85% TSS removal and 87% turbidity reduction. Particle Size Analyzer (PSA) results indicated that PAC produced larger and more uniform flocs (Xav = 1796.71 nm; PI = 0.403) compared to chitosan (Xav = 1070.28 nm; PI = 0.444). Although PAC had slightly higher efficiency, chitosan from mussel shell waste shows strong potential as an environmentally friendly coagulant for treating river water. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and Communities